Design and development of anti-gridlock system for monitoring and alerting based on automation and image processing - et. al., Shivanandam K, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now–a-days the aggregation of moving vehicles, in any locality or area has increased exponentially, with the current number of vehicles on roads having exceeded all estimates and predictions. Consequently, an increase in traffic density has been observed, leading to a number of road accidents, some fatal, some serious, … Accidents, howsoever minor or major, cause cumbersome traffic jams which throws normal movement as well as life, totally out of rhythm. The rarest of all commodities, precious ‘Time’ is lost which adds to man’s misery and overall stress in life. All of which is avoidable. To provide a solution to the above said problems, an approach has been designed having a smart automated system with smart displays working on the Internet of Things (IoT) and Image Processing. This approach is finely integrated with 4 different technical concepts.The approach consists of the following procedures: (a) It includes a solar panel which tracks the intensity of sunlight, and follows it too, to increase the power efficiency, (b) An automated street light which works on the basis of light intensity to save energy, along with an automatic circuit fault detection with feedback system for the street lights which alerts the public and respective government agency, (c) So as to ensure that the moving vehicles don't cross the zebra crossing when the traffic signal is RED, a cam is used for image processing to detect and alert vehicles/people not to break the rules and thereby avoid accidents and (d) An arrangement to monitor the level of drainage water in sewer lines, to alert the public and the respective authorities when it is almost full and overflowing onto streets / roads resulting in disruption of smooth traffic movement.Thus, the above approach is proposed as a solution to the common problems faced by man on the roads.